Pengaruh Jumlah Ekstraksi Bertingkat Terhadap Yield Antosianin pada Kulit Buah Naga Merah (Hylocereus polyrhizus) - Siti Khuzaimah; Nuril Millati (Jurnal Ilmiah Teknik Kimia, 2022)
Dragon fruit skin has a very attractive red color that has the potential to produce anthocyanin pigments. Anthocyanin pigments are flavonoid compounds that are soluble in water and can be used as natural dyes in food and beverages. The purpose of this study was to see the effect of the number of multilevel extraction on the anthocyanin yield of dragon fruit peel extraction. 20 grams of dragon fruit peel powder with a mesh size of 20 was extracted in batches for 72 hours at room temperature using a mixture of distilled water and 10% citric acid (1:6) as a solvent. Variations in the number of stratified extractions were 1,2,3,4 and 5 times of extraction with the number of solvents respectively 500, 2 x 250 ml, 3 x 167 ml, 4 x 125 ml, and 5 x 100 ml. analysis of anthocyanin pigment levels using a spectrophotometer with a different pH method. The results obtained that the anthocyanin yield with samples 1 to 2 times of extraction increased by 6.35%, while the anthocyanin yield of samples 1 to 5 times of extraction increased by 35.65%. The highest yield of anthocyanin pigments was 4.1625 mg/20 grams in a multilevel extraction carried out for 5 times of extraction.